2012
DOI: 10.1371/journal.pone.0044728
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Regulatory T Cells among Tuberculosis Patients: Impact on Prognosis and Restoration of Antigen Specific IFN-γ Producing T Cells

Abstract: CD4+CD25+Foxp3+ Regulatory T cells (Treg) and programmed death-1 (PD-1) molecules have emerged as pivotal players in immune suppression of chronic diseases. However, their impact on the disease severity, therapeutic response and restoration of immune response in human tuberculosis remains unclear. Here, we describe the possible role of Treg cells, their M. tuberculosis driven expansion and contribution of PD-1 pathway to the suppressive function of Treg cells among pulmonary tuberculosis (PTB) patients. Multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 51 publications
(100 reference statements)
13
57
0
Order By: Relevance
“…No significant effects were measured on IFN-γ or IL-17. These results are consistent with those of previous studies in other diseases (19), suggesting that sPD-L1 inhibits Th1 immune responses and supports the Th2 immune response, resulting in a stronger Th2 immune response.…”
Section: Effect Of Spd-l1 On Lymphocyte Cytokine Production and Prolisupporting
confidence: 93%
“…No significant effects were measured on IFN-γ or IL-17. These results are consistent with those of previous studies in other diseases (19), suggesting that sPD-L1 inhibits Th1 immune responses and supports the Th2 immune response, resulting in a stronger Th2 immune response.…”
Section: Effect Of Spd-l1 On Lymphocyte Cytokine Production and Prolisupporting
confidence: 93%
“…With regard to the relation between Treg cells and TB, one report states that patients with TB have more Treg cells in their peripheral blood compared with healthy controls [12]. Another study demonstrated that Treg-cell-depleted mice infected with TB have a low bacterial load in the lungs after aerosol infection [13].…”
Section: Discussionmentioning
confidence: 99%
“…The production of IL-10 was increased among infected individuals and Treg cells are found to be one of the dominant producers of IL-10 [41,42,54,128,[172][173][174] (Figure 3). Increased level of IL-10 producing Treg cells offers a conducive platform form reactivation of latent TB infection and its progression in disseminated form of TB [175][176][177][178]. It is also demonstrated that the blocking of IL-10 with anti-IL-10 Ab restores the effector immune response.…”
Section: Orchestration Of Cellular Immune Response Against Hivmentioning
confidence: 99%